CHALLENGES AND SOLUTIONS IN QURANIC MEMORIZATION REVISION AMONG TAHFIZ STUDENTS: A SYSTEMATIC LITERATURE REVIEW - Md Yusup, Norafidah; Junus, Qatrunnada (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This systematic literature review aims to explore the challenges and solutions in Quranic memorization revision among Tahfiz students. One of the most important components of Islamic education is memorizing the Quran, but students face major challenges in either revising the memorized verses or retaining them. This happens due to a number of reasons, such as lack of adequate institutional support, ineffective pedagogy, and curriculum-related issues. Using the PRISMA framework for data extraction and analysis, this study conducts advanced searches in Scopus and ERIC databases to address these challenges, identifying relevant articles and ultimately including 18 primary studies (n=18) in the final review. The results are divided into three themes: (1) Challenges and Opportunities in Islamic Education, (2) Pedagogy and Philosophy of Islamic Education, and (3) Curriculum and Institutional Development in Islamic Education. The findings point to the complex nature of the obstacles encountered by Tahfiz students, from personal to structural, such as with motivation and concentration, as well as insufficient qualified teaching staff and limited resources. The opportunities for improvement identified include the integration of modern pedagogical techniques into the varying modes of delivery, the adoption of available digital tools, and stronger institutional support. This has resulted in the recommendation that a holistic approach is necessary to address these challenges, as it includes curriculum reforms, teacher training, and the need to integrate new technologies to assist the Quranic memorization process to ensure its success and sustainability. Realising these hindrances and addressing them can enhance the revision process of Quran memorisation among Tahfiz students and benefit the students and the Islamic educational community at large.